Keputusan Mahkamah Konstitusi Tentang Pemungutan Suara Ulang Pemilihan Kepada Daerah Serentak 2020 Sebagai Perwujudan Demokrasi - Esti ningrum; wahyu hariadi (Wijayakusuma Law Review, 2022)
The number of applications for re-voting (PSU) granted by the Constitutional Court (MK) in 16 regions in the 2020 Simultaneous Regional Head Elections (Pilkada), this is the largest number since the 2015 simultaneous Pilkada era. In 2015 there were 4 requests granted, year In 2017 there were 6 requests that were granted and in 2018 there were 5 requests that were granted. The purpose of this research is to analyze whether the decision of the Constitutional Court regarding Re-Voting for the 2020 Simultaneous Regional Elections is a manifestation of democracy from people's sovereignty. The method used in this research is doctrinal legal research through statutory and case approaches. The success of the Regional Head Election (Pilkada) as a parameter of democracy does not lie in the presence or absence of Pilkada, but rather in the quality of the implementation of the Pilkada itself. This means that regional elections are carried out in accordance with four concepts, namely regional elections as a means of people's sovereignty, carried out in a liberal and fair manner, carried out in the Unitary State of the Republic of Indonesia, and carried out based on Pancasila and the 1945 Constitution. elections that have integrity, professionalism and accountability. Democratic Pilkada is a value mandated in Law Number 10 of 2016 concerning the Second Amendment to Law Number 1 of 2015 concerning the Stipulation of Government Regulations in Lieu of Law Number 1 of 2014 concerning the Election of Governors, Regents and Mayors to Become Laws. Democratic values in their implementation sometimes do not materialize in their implementation, the Constitutional Court as the guardian of democracy can issue a decision to carry out a Re-Vote. Pilkada So that the re-voting is part of the embodiment of democracy which must be carried out properly. Keywords: Constitutional Court, Re-voting, Regional Head Election, Democracy Jumlah permohonan Pemungutan Suara Ulang (PSU) yang dikabulkan oleh Mahkamah Konstitusi (MK) sejumlah 16 daerah pada Pemilihan Kepala Daerah (Pilkada) Serentak tahun 2020, ini merupakan jumlah terbanyak sejak era Pilkada serentak tahun 2015. Tahun 2015 ada 4 permohonan yang dikabulkan, tahun 2017 ada 6 permohonan yang dikabulkan dan tahun 2018 ada 5 permohonan yang dikabulkan. Tujuan penelitian ini adalah untuk menganalisa apakah keputusan Mahkamah Konstitusi tentang Pemungutan Suara Ulang Pemilihan Daerah Serentak tahun 2020 sebagai perwujudan demokrasi dari kedaulatan rakyat. Adapun metode yang digunakan dalam penelitian ini adalah penelitian hukum doktrinal dengan melalui pendekatan perundang-undangan dan pendekatan kasus. Keberhasilan Pemilihan Kepala Daerah (Pilkada) sebagai parameter demokrasi bukanlah terletak pada ada atau tidak adanya Pilkada, namun lebih pada kualitas pelaksanaan Pilkada itu sendiri. Artinya Pilkada dilaksanakan sesuai dengan empat konsep yaitu Pilkada sebagai sarana kedaulatan rakyat, dilaksanakan secara Luber dan Jurdil, dilaksanakan dalam Negara Kesatuan Republik Indonesia, dan dilaksanakan berdasarkan Pancasila dan UUD 1945. Dengan berlandaskan pada konsep tersebut penyelenggaraan Pilkada yang demokratis dapat terwujud apabila dilaksanakan oleh penyelenggara pemilihan umum yang mempunyai integritas, profesionalisme dan akuntabilitas. Pilkada yang demokratis merupakan nilai telah yang diamanatkan dalam Undang-Undang Nomor 10 Tahun 2016 tentang Perubahan Kedua Atas Undang-Undang Nomor 1 Tahun 2015 tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang Nomor 1 Tahun 2014 tentang Pemilihan Gubernur, Bupati dan Walikota Menjadi